The Role of Self-Control in Moderating the Influence of Shopping Lifestyle and Hedonistic Behavior on Impulsive Buying (A Study on Gurlbucket Consumers in Shopee E-commerce, Denpasar City) - Geoffrey Vigo Lienardy; I Gede Nandya Oktora Panasea (CV. Lenggogeni Data Publishing, 2026)
The rapid growth of e-commerce has driven changes in consumer behavior, particularly in impulsive buying. This study aims to determine the role of self-control in moderating the influence of shopping lifestyle and hedonic behavior on impulsive buying among Gurlbucket consumers on Shopee in Denpasar City. This research used a quantitative approach with a non-probability sampling method and purposive sampling technique involving 160 respondents. Data were analyzed using Moderated Regression Analysis (MRA) with the assistance of SPSS. The results show that shopping lifestyle has a positive but insignificant effect on impulsive buying, while hedonic behavior has a positive and significant effect. Self-control was found to weaken the effect of shopping lifestyle on impulsive buying, although insignificantly, and significantly weaken the effect of hedonic behavior on impulsive buying. These findings indicate that self-control plays an important role in regulating consumer impulsive behavior in online shopping activities.